Determining and overcoming resistance to HIV protease inhibitors - Prejdová, Jana; Soucek, Milan; Konvalinka, Jan (Current drug targets. Infectious disorders, 2004)
HIV protease represents a major target for development of antiviral therapeutics. The introduction of HIV protease (PR) inhibitors (PIs) to clinical practice and the application of highly active antiretroviral therapy resulted in decreased mortality and prolonged life expectancy of HIV-positive patients. However, the high polymorphism of HIV leads to rapid selection of viral variants resistant towards the inhibitors. Such resistant PR variants have developed in HIV-positive patients after treatment with any of the eight PIs approved for clinical use. In this review we overview (i) the methods for the identification and assessment of viral resistance in HIV positive patients, and (ii) the approaches medicinal chemists take to overcome it. Rational antiviral therapy brings about the need for quantitative assessment of the level of drug resistance development in the course of the treatment. At present, two main approaches are taken: in genotypic assays the viral sequences are PCR amplified, sequenced and changes in the viral gene sequence known to be associated with reduced drug sensitivity are identified, while phenotypic assays test the ability of a virus to grow in the presence of a drug or combination of drugs. The advantages and drawbacks of these methods, as well as their relevance for the therapy are discussed. We also review the efforts to design second-generation PIs, capable of potently inhibiting multi-resistant HIV-1 PR species, using structure-assisted design of the compounds targeted to the active site, as well as alternative approaches with compounds binding to other domains of the PR molecule.
Keywords: HIV; inhibitory HIV-proteasy; fenotyp; Phenotype; replikace viru; Genotype; HIV Infections; racionální návrh léčiv; HIV Protease Inhibitors; HIV infekce; Drug Resistance, Viral; lidé; Virus Replication; dimerizace; Humans; Drug Design; virová léková rezistence; genotyp; Dimerization